Regulation of immune responses by RasGEF1B circular RNA / Ng Wei Lun - Ng , Wei Lun (2017)
Circular RNAs (circRNAs) constitute a large class of RNA species formed by the back-splicing of co-linear exons, often within protein-coding transcripts. Despite much progress in the field, it remains elusive whether the majority of circRNAs are merely aberrant splicing by-products with unknown functions, or their production is spatially and temporally regulated to carry out specific biological functions. To date, the majority of circRNAs have been cataloged in resting cells. Here, this research identifies a LPS-inducible circRNA: mcircRasGEF1B, which is predominantly localized in cytoplasm, shows cell-type specific expression, and has a human homolog with similar properties, hcircRasGEF1B. The functional experiments show that knockdown of the expression of mcircRasGEF1B reduces LPS-induced ICAM-1 expression. Additionally, this study demonstrates that mcircRasGEF1B regulates the stability of mature ICAM-1 mRNAs. To gain broader insights of mcircRasGEF1B function during cellular response to LPS stimulation, targeted mcircRasGEF1B depletion with high-throughput transcriptomic analysis is combined. The results show that knockdown of mcircRasGEF1B results in altered expression of a wide array of genes. Pathway analysis reveals an overall enrichment of genes involved in cell cycle progression, mitotic division, active metabolism, and of particular interest, NF-κB, LPS signaling pathways and macrophage activation. These findings expand the inventory of functionally characterized circRNAs with a novel RNA species that may play a critical role in fine-tuning immune responses during macrophage activation and protecting cells against microbial infection.